Net Foreign Direct Investment Development Path of the EU Member States - Sanja Franc (Ekonomski Vjesnik, 2013)
The main objective of this research was to investigate the relationship between net foreign direct investment outflow and economic development on a sample of the European Union (EU) Member States and the Republic of Croatia which is soon to become a full member of the EU. The main hypothesis was that EU Member States are heterogeneous and at various stages of foreign direct investment development path. The research included five independent variables to determine an approximate level of economic development: “GDP per capita”, “FDI inflows per capita”, “exports”, “number of Internet users”, and “number of enrolments in tertiary education”. The results of the empirical analysis have confirmed the assumptions behind Dunning’s model of investment development path that there is a relationship between net foreign direct investment outflow and economic development, thus confirming the main hypothesis that the EU Member States are heterogeneous and that they are at different stages of foreign direct investment development path.